Social Networking Sites Usage as Learning Platform for Business Education Students in Federal Colleges of Education in North East, Nigeria - Umar, B. Y.; Hayatu, , S.; Idi, S. (Kashere Journal of Education, 2021)
This study assessed social networking sites usage as a learning platform for business education students in Federal colleges of education in Northeast Nigeria. Descriptive survey research design was adopted a structured questionnaire was used for data collection. The area of the study comprises three Federal Colleges of education in Northeast Nigeria they are: Federal College of education Technical Gombe, Federal College of education Technical Potiskum, and Federal College of education Yola. The population of the study comprised 709 NCE II business education students. 253 students were selected and used as sample of the study Questionnaire was used as instrument for data collection and was validated by three experts. To determine the internal consistency of the instrument, Cronbach alpha technique was used and a reliability coefficient of 0.79 was obtained and found to be reliable. The instrument was administered by the researcher with the help of three research assistants. Mean and standard deviation were used for the analysis of data collected. The Mean statistic and standard deviation were used to answer the research questions. The findings of the study showed that: social networking tools are not used for accessing educational materials among students and the sites has negative effect among students in Federal Colleges of education in Northeast Nigeria. The study therefore, recommended among others that: Students should through various means learn and used social networking tools to access and share different educational materials among themselves, negative usage of social networking sites among students should be avoided.